Analisis Wacana Kritis Media Online Bali Post Terhadap Isu Sampah Upakara Hindu di Bali - I Gede Titah Pratyaksa; Niluh Wiwik Eka Putri (Jurnal Penelitian Agama Hindu, 2026)
The issue of Hindu ritual waste in Bali has increasingly attracted public attention due to its implications for environmental sustainability, religious practices, and the tourism sector, while also being extensively represented in local media discourse. This study aims to analyze the construction of discourse surrounding Hindu ritual waste in Bali Post online news coverage, identify the representation of social actors, and uncover the underlying ideologies embedded within the reporting practices. The research employs a descriptive qualitative approach using Norman Fairclough’s Critical Discourse Analysis framework, which encompasses three dimensions: text, discursive practice, and social practice. The data consist of four Bali Post news articles published in 2025 that discuss Hindu ritual waste in various religious contexts across Bali. The findings reveal that, at the textual level, the news coverage is dominated by persuasive, educational, and solution-oriented language that links religious practices to ecological responsibility. At the level of discursive practice, news sources are primarily drawn from government officials, traditional authorities, and environmental management institutions, resulting in the predominance of official perspectives over those of community members and critical groups. At the level of social practice, the reporting reproduces a discourse of harmony between the preservation of Hindu traditions and environmental management, while reinforcing ideologies of cultural ecologicalization, environmental managerialism, and the normalization of waste-related issues through institutional legitimacy. This study concludes that Bali Post functions not merely as a provider of information but also as a discursive actor that shapes public understanding of the relationship between religion, culture, the environment, and waste management policies in Bali.